The Impact of Sport Training on Oral Health in Athletes - Domenico Tripodi; Alessia Cosi; Domenico Fulco; Simonetta D'Ercole (MDPI AG, 2021)
Athletes' oral health appears to be poor in numerous sport activities and different diseases can limit athletic skills, both during training and during competitions. Sport activities can be considered a risk factor, among athletes from different sports, for the onset of oral diseases, such as caries with an incidence between 15% and 70%, dental trauma 14-70%, dental erosion 36%, pericoronitis 5-39% and periodontal disease up to 15%. The numerous diseases are related to the variations that involve the ecological factors of the oral cavity such as salivary pH, flow rate, buffering capability, total bacterial count, cariogenic bacterial load and values of secretory Immunoglobulin A. The decrease in the production of S-IgA and the association with an important intraoral growth of pathogenic bacteria leads us to consider the training an "open window" for exposure to oral cavity diseases. Sports dentistry focuses attention on the prevention and treatment of oral pathologies and injuries. Oral health promotion strategies are needed in the sports environment. To prevent the onset of oral diseases, the sports dentist can recommend the use of a custom-made mouthguard, an oral device with a triple function that improves the health and performance of athletes. During training, the sports dentist must monitor the athletes and the sports examination protocol must be implemented with the inclusion of the clinical examination, quantitative and qualitative analysis of saliva and instructions on the use, cleansing and storage of the mouthguard.